2015
DOI: 10.1007/s10439-015-1403-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Healthy Myocardium in Diastole

Abstract: In order to better understand the mechanics of the heart and its disorders, engineers increasingly make use of the finite element method (FEM) to investigate healthy and diseased cardiac tissue. However, FEM is only as good as the underlying constitutive model, which remains a major challenge to the biomechanics community. In this study, a recently developed structurally based constitutive model was implemented to model healthy left ventricular myocardium during passive diastolic filling. This model takes into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The animals used in this work received care in compliance with the protocols approved by the Institutional Animal Care and Use Committee at the University of Pennsylvania in accordance with the guidelines for humane care (National Institutes of Health Publication 85-23, revised 1996). The data used in the current study is from the same animal cohort that was used in the study of Nikou et al [9], in which many of the experimental details can be found. Briefly, the endocardium and epicardium of the LV were contoured from the 3D SPAMM (SPAtial Modulation of Magnetization) MR images and fit with 3D surface geometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The animals used in this work received care in compliance with the protocols approved by the Institutional Animal Care and Use Committee at the University of Pennsylvania in accordance with the guidelines for humane care (National Institutes of Health Publication 85-23, revised 1996). The data used in the current study is from the same animal cohort that was used in the study of Nikou et al [9], in which many of the experimental details can be found. Briefly, the endocardium and epicardium of the LV were contoured from the 3D SPAMM (SPAtial Modulation of Magnetization) MR images and fit with 3D surface geometry.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the passive material parameters (C, b f , b t , b fs ) were optimized within the ranges previously reported for normal myocardium [12]. Diastolic strain was calculated from the 3D SPAMM MR images using a custom optical flow plug-in for ImageJ to derive 3D displacement flow fields [9]. The objective function that was minimized during the optimization was taken to be the mean squared error (MSE) between MRI measured and FE predicted strains as well as the normalized difference in LV cavity volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the sheet structure) of the myocardium has surfaced more recently (Arts et al, 2001), (Ashikaga et al, 2005), (Ashikaga et al, 2008), (Chen et al, 2005), (Cheng et al, 2005), (Cheng et al, 2008), (Coppola and Omens, 2008), (Costa et al, 1999), (Covell, 2008), (Nikou et al, 2015), (Pope et al, 2008). Since it is commonly argued that sheet structures contribute to wall thickening by allowing large shear deformations to occur (Costa et al, 1999), (Cheng et al, 2005), the orientation, dispersion, and mechanical properties of these sheets are undoubtedly important factors contributing to fiber stress and strain.…”
Section: Transmural Gradients As Mechanisms Of Uniform Fiber Stresmentioning
confidence: 99%
“…However, most of these studies have focused on one region only, namely, the LV (Nikou et al, 2016, Wise et al, 2016. The stress-strain curve of the LV has then been used as being representative of the whole heart.…”
Section: Discussionmentioning
confidence: 99%